2016
DOI: 10.18552/2016/scmt4s239
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of Concrete Using Seawater and By-product Aggregates

Abstract: Authors developed concrete using seawater as mixing water. A combination of sea water, ordinary portland cement, ground granulated blast-furnace slag, fly ash, silica fume, and a special chemical admixture containing calcium nitrite was adopted to densify concrete. This concrete is hereafter referred to as "concrete with seawater". This technology not only improves the performance of concrete but also shortens the material transportation process and reduces cost and CO2 emission from construction work by effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recent findings also confirm the similar results regarding the positive effect of SW mixing on the early strength and a minor degrading impact on the later strength of concrete [8,9]. The salt content in SW concrete usually has a declining effect on the properties of fresh concrete, resulting in reduced workability and quicker setting [10][11][12]. However, certain studies [12,13] suggest that the appropriate use of chemicals and mineral admixtures (metakaolin, fly ash, GGBFS) can improve the workability of SW concrete.…”
Section: Introductionsupporting
confidence: 72%
“…Recent findings also confirm the similar results regarding the positive effect of SW mixing on the early strength and a minor degrading impact on the later strength of concrete [8,9]. The salt content in SW concrete usually has a declining effect on the properties of fresh concrete, resulting in reduced workability and quicker setting [10][11][12]. However, certain studies [12,13] suggest that the appropriate use of chemicals and mineral admixtures (metakaolin, fly ash, GGBFS) can improve the workability of SW concrete.…”
Section: Introductionsupporting
confidence: 72%
“…The mix proportion used to make SWSSC also has significant effect on its fresh and hardened properties [22]. Furthermore, the addition of mineral admixtures such as fly ash and blast furnace slag also has the potential to enhance the compressive and tensile strengths of SWSSC [3,23]. The properties of SWSSC used in confinement studies are summarised in As summarised in Table 1, naturally available coarse aggregates have been employed in majority of the studies focusing on confined SWSSC.…”
Section: Properties Of Swssc Used In Confinement Studiesmentioning
confidence: 99%
“…The microstructure of concrete with sea sand and sea water shows a denser structure, which has a positive effect on concrete durability [29]. Study [30] found that sea concrete had high water tightness and frost resistance due to its denser structure compared to conventional concrete. Shrinkage deformations of sea concrete tend to increase, as described by the authors [31][32][33][34].…”
Section: The Ocean As a Source Of Basic Concrete Constituentsmentioning
confidence: 99%